A Framework for the Simultaneous Measurement of Spatial Variation and Temporal Movement in Prices in a Heterogeneous Country: The Dynamic Household Regional Product Dummy Model. (20th February 2017) - Chakrabarty, Manisha; Majumder, Amita; Ray, Ranjan
Abstract : This paper contributes to the growing literature on spatial prices in large heterogeneous countries. While the literatures on spatial variation and temporal movement in prices have grown in parallel, this study marks a departure by providing a unified treatment and proposing a comprehensive framework that allows both approaches. The proposed model is based on twin extensions of the household version of the "country product dummy model" by allowing for a dynamic stochastic specification and interdependence of spatial prices of geographically adjacent regions. Tests of temporal stability and regional independence of the estimated spatial prices are proposed and applied in this paper. The paper shows that the introduction of an autoregressive error process of order one, AR(1), improves the efficiency of the estimates of parameters, urban‐rural and temporal price indices under certain conditions. The Indian application points to a rich potential for using the proposed framework in cross country comparisons such as the International Comparison Program (ICP) exercises.